Alkynyl bridged cyclometalated Ir2M2 clusters: impact of the heterometal in the photo- and electro-luminescence properties. Issue 8 (1st February 2016) - Fernández-Cestau, Julio; Giménez, Nora; Lalinde, Elena; Montaño, Patricia; Moreno, M. Teresa; Sánchez, Sergio; Weber, Michael D.; Costa, Rubén D.
Abstract : The distinct photo- and electro-luminescence properties of clusters [Ir2 M2 (ppy)4 (μ-CCC6 H4 -OMe3 )4 ] (M = Ag, Cu) provide an example of the role of the CCR groups in modulating metallophillic bonding in the T1 state. Abstract : We report two unprecedent alkynyl bridging cyclometalated clusters [Ir2 M2 (ppy)4 (μ-CCC6 H4 -OMe3 )4 ] where M is Ag (2 ) and Cu (3 ), which display distinctive luminescence properties. While2 features a green phosphorescence/electroluminescence nature located at the ppy ligands ( 3 LC), 3 shows an orange emission confined to the metals and alkynyl groups having a mixed 3 L′C/ 3 L′MCT/ 3 MMCT (L′ = alkynyl) nature.